Lighting a Lamp: Citizenship Behavior and Social Capital - Upadhyay, Divya (Prabandhan: Indian Journal of Management, 2011)
In the present paper, an attempt has been made to link dimensions of citizenship behaviours with dimensions of social capital. For studying dimensions of citizenship behaviour, two frameworks have been used: 1) Podsakoff, KacKenzie, and Paine, Bachrach (2000) which divides citizenship behaviour into seven dimensions and 2) Van Dyne, Graham, and Dienesch (1994) which divides citizenship behaviour into five dimensions. For studying social capital, Nahapiet and Ghoshal (1998) framework has been used, which divides social capital into three dimensions: structural, cognitive and relational. A theoretical framework is developed to see which dimension of Organization Citizenship Behaviour (OCB) will be positively related to social capital dimensions, and simultaneously, propositions have been developed. The basic proposition is that OCBs facilitate the development of structural, relational, and cognitive dimensions of social capital among employees. The framework presented here suggests that different forms of citizenship contribute to the creation of the relational, cognitive, and structural aspects of social capital in different ways. The model also suggests that social capital may, in turn, stimulate additional citizenship behaviours. For future research, OCB and social capital can be linked to three network types proposed by Inkpen and Tsang (2005). In their paper, they studied three types of networks from the single-node divisionalized firm (the intracorporate network) to interfirm relationships (the alliance) to an unstructured collection of firms (industrial district).